(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article discusses modern philosophical concepts of civilization development of society, state and power. The actuality of the article is attempt of the author for substation his own idea of the modern civilization conception based on such famous philosopher’s as Berdyaev, Sorokin, Toinby, Shumpeter, Reisner and many other scientists. As follows from the philosophical analysis of this concept idea, the basis of progressive social developmen is a modern democratic society. The methods of scientific and theoretical comparative research, used by the author, made it possible to show the particular significance of the philosophical analysis of the concept of modern civilization. Among the main conditions for the modernization of society, according to the researh, the openness of society, its operational informatisation, the dynamics of economic growth, the growing role of culture in social activities, the introduction of new social skills are. The article could be interesting both theoretically and practically. The some results of the philosophical analysis, carried out by the author, can be used to determine the philosophical direction of the development of modern Kazakh civilization, the solution of some social, spiritual and practical issues arising in modern Kazakhstan society. Key words: experiment, hegemony, formation, civilization, component, globalization, integral, prosperity, secularization, declarisation, gravity.